Do Teachers Have Different Mental Representations of Relationships With Children in Cases of Hyperactivity Versus Conduct Problems?. Issue 4 (1st December 2019) - Bosman, Rianne J.; Zee, Marjolein; Koomen, Helma M. Y.
Abstract: The present study examined how different externalizing child behaviors (i.e., hyperactivity, conduct problems) were uniquely associated with teachers' mental representations of relationships with individual children. Participants were 61 teacher–child dyads from typical Dutch elementary schools. Using a two-wave design, teachers first reported about a child's behavior. Four months later, they were interviewed using the Teacher Relationship Interview to assess relationship representations. The Teacher Relationship Interview was rated by coders on 9 constructs that comprised 3 dimensions: content (e.g., sensitive practices of teachers); affect (e.g., positive and negative feelings); and process (e.g., coherence of narratives). Regression analyses revealed that teachers had higher levels of positive affect and sensitive practices when it came to hyperactivity, whereas teachers experienced more anger when it came to conduct problems. The results indicate that hyperactivity and conduct problems may uniquely contribute to teachers' mental representations of their relationships with children.